The Engagement of Iceland and Malta with European Integration: Economic Incentives and Political Constraints - Magnús Árni Magnússon 1968- (2011)
This dissertation is on the different routes Iceland and Malta have taken towards European integration in the period 1989-2009, despite significant opposition towards European integration in both countries. It is the general purpose of it to apply and test one of the academic frameworks explaining the dynamic of integration in countries where widespread scepticism is towards the European project, the framework of Sieglinde Gstöhl, in which is combined an analysis of economic interests in market integration with ideational interests in protecting national identity, and use it to explain the routes Malta and Iceland have taken towards EU membership.